1979
DOI: 10.1210/jcem-49-4-652
|View full text |Cite
|
Sign up to set email alerts
|

PULSATILE SUBCUTANEOUS NOCTURNAL ADMINISTRATION OF GnRH BY PORTABLE INFUSION PUMP IN HYPOGONADOTROPIC HYPOGONADISM: INITIATION OF GONADOTROPIN RESPONSIVENESS.

Abstract: GnRH was administered subcutaneously in hourly pulses for 10 consecutive nights to two immature males with Kallmann's Syndrome using a portable, battery-operated infusion pump adapted for home use. Pulsatile GnRH produced a progressive increase in urinary gonadotropin excretion, a significant increase in mean basal plasma FSH, pulsatile LH release, and an increased LH response to a standard 3 hour GnRH infusion test. One subject developed a striking increment in plasma testosterone in response to GnRH pulses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…In an effort to elucidate the nature of these changing responses we have previously administered low doses of GnRH in a pulsatile manner, to mimic the presumed physiological pattern of GnRH secretion, to female patients with absent or greatly reduced endogenous GnRH secretion. Our results (4,5) and those of others (6,7) have shown that the initial response to GnRH is one of predominant FSH secretion that later declines, while LH responses gradually increase. This pattern seen over 5 d of pulsatile GnRH injections is similar to that present during sexual maturation in girls.…”
Section: Introductionsupporting
confidence: 75%
“…In an effort to elucidate the nature of these changing responses we have previously administered low doses of GnRH in a pulsatile manner, to mimic the presumed physiological pattern of GnRH secretion, to female patients with absent or greatly reduced endogenous GnRH secretion. Our results (4,5) and those of others (6,7) have shown that the initial response to GnRH is one of predominant FSH secretion that later declines, while LH responses gradually increase. This pattern seen over 5 d of pulsatile GnRH injections is similar to that present during sexual maturation in girls.…”
Section: Introductionsupporting
confidence: 75%
“…Also, a notable feature of the present study was that pulsatile GnRH treatment in OVX-HPD ewes did not consistently produce pulsatile FSH se cretion. A similar pulsatile GnRH regimen produced pulsa tile FSH release in patients with anorexia nervosa [14] but this is not always observed in GnRH-treated hypogonadal subjects [19,25]. In the sheep, GnRH appears to provide a trophic stimulus for FSH secretion but the direct secretory relationship that exists for GnRH and LH [9] is not appar ent for FSH.…”
Section: Discussionmentioning
confidence: 99%
“…A pulsatile GnRH stimulus appears to be essential for gonadotropin secretion to be manifest. If GnRH is given to GnRH-deficient humans or hypothalamic lesioned monkeys in a pulsatile manner, the normal hormonal changes of puberty or the menstrual cycle can be reproduced (9)(10)(11)(12)(13)(14)(15)(16). On the other hand, continuous infusion of GnRH to lesioned monkeys results in "down-regulation" of gonadotropin secretion, which is restored by reinstitution of a pulsatile stimulus (17).…”
Section: Introductionmentioning
confidence: 99%